Natural Killer Cell Development and Maturation Revisited: Possible Implications of a Novel Distinct Lin−CD34+DNAM-1brightCXCR4+ Cell Progenitor - Bozzano, Federica; Marras, Francesco; De Maria, Andrea (Frontiers in Immunology, 2017)
Since the first description of Natural Killer cells (NK) the view on their role in innate immunity has evolved considerably. In addition to first-line defense against transformed and pathogen-infected autologous cells NK cells contribute to modulate adaptive immune responses and in some cases acquire specialized functions including exhausted, adaptive and decidual NK cells. NK cells derive from CD34+ progenitors, in vivo and in vitro, however it is unclear whether the high phenotype diversity in vivo may be generated from these precursors alone. The recent characterization of a novel CD34+DNAM-1brightCXCR4+ precursor giving rise to apparently licensed and functional maturing NK cells may suggest the possibility for a higher than expected common lymphocyte precursor diversity and a consequently higher peripheral NK cell phenotype variability. Here we review the evidences on NK cell central and peripheral development from CD34+ precursors and propose a possible updated reading frame based on the characterization of CD34+DNAM-1brightCXCR4+ cell progenies which favors the possibility of concurrent NK cell maturation from different CD34+ precursors.